1988
DOI: 10.1164/ajrccm/138.2.355
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Mechanics during the First Day of Mechanical Ventilation in Patients with Pulmonary Edema and Chronic Airway Obstruction

Abstract: We investigated the early changes of respiratory mechanics in mechanically ventilated patients with acute respiratory failure (ARF): 8 patients after acute exacerbation of chronic airway obstruction (CAO), 8 patients with cardiogenic pulmonary edema (CPE), and 8 patients with adult respiratory distress syndrome (ARDS). The patients were studied within the first day from the onset of mechanical ventilation. Flow, changes in lung volume, and airway pressure were measured using the 900C Servo Ventilator. End-insp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
91
0
3

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(99 citation statements)
references
References 10 publications
5
91
0
3
Order By: Relevance
“…Respiratory compliance or elastance and airway resistance can be readily calculated using the flow and pressure transducers incorporated into modern mechanical ventilators, if the raw signals can be connected to an external recording device (21). Among these, the constant flow inflation method has been employed by many authors (12,13,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory compliance or elastance and airway resistance can be readily calculated using the flow and pressure transducers incorporated into modern mechanical ventilators, if the raw signals can be connected to an external recording device (21). Among these, the constant flow inflation method has been employed by many authors (12,13,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the expiration, this positive pressure is termed auto positive end-expiratory pressure (auto PEEP) or intrinsic positive end-expiratory pressure (PEEPi) [2,3]. PEEPi and dynamic hyperinflation have been described in mechanically-ventilated chronic obstructive pulmonary disease (COPD) patients, in whom expiratory flow limitation had occurred as a consequence of dynamic airway compression [1][2][3][4][5][6][7][8]. Recent studies have suggested that, in COPD patients with expiratory flow limitation, the application of external PEEP during assisted mechanical ventilation [9], or the use of continuous positive airway pressure (CPAP) in spontaneously breathing patients [10], can counterbalance and reduce the inspiratory threshold load imposed by PEEPi, without causing further hyperinflation.…”
mentioning
confidence: 99%
“…Accordingly, in COPD, the thresholds for fR and V 'E were necessarily lower than those obtained by YANG and TOBIN [1] in a nonhomogeneous population (table 2). In the present COPD patients, the Crs,st measured during mechanical ventilation were relatively high (table 3), reflecting the fact that, in COPD patients with ARF, the Crs,st does not differ significantly from that of normal subjects [4,10], except on the first day of mechanical ventilation, when they exhibit marked dynamic hyperinflation and hence their VT impinges on the flat upper part of the static volume/pressure curve of the respiratory system [2]. It should be noted, however, that during spontaneous breathing trials COPD patients may exhibit markedly enhanced dynamic hyperinflation (DH) with concomitant decrease in Crs,st.…”
Section: Discussionmentioning
confidence: 54%